A RE-EXAMINATION AND RE-INTERPRETATION OF TIDE GAUGE DATA FOR CHURCHILL, MANITOBA - Barnett, D.M. (Canadian Journal of Earth Sciences, 1966)
Tide gauge data from Churchill, Manitoba, for the period 1928–1939 are reviewed and rejected as inaccurate. The rate of uplift proposed by Gutenberg on the basis of these data therefore is rejected also. Data from 1940 to 1964 are subjected to statistical analysis, which indicates an apparent lowering trend of water level. Linear regression suggests a rate of 2 ft per century.